Самые знаменитые сказки для самых маленьких - Егунов Игорь (Эксмо, 2010)
Экземпляры: ф12 (20201029) / Инвентарный номер: 60459 / Цена: 296.00 / Сис.шифр: Д / Авт.знак: С 17 / ГРНТИ: 17.82.93 / ББК: 84(0)